Quantifying the Shift Toward Transcatheter Aortic Valve Replacement in Low-Risk Patients: A Meta-Analysis. Issue 6 (June 2017) - De Sciscio, Paolo; Brubert, Jacob; De Sciscio, Michele; Serrani, Marta; Stasiak, Joanna; Moggridge, Geoff D.
Abstract : Background—: In recent years, use of transcatheter aortic valve replacement has expanded to include patients at intermediate- and low-risk cohorts. We sought to determine disease prevalence and treatment distribution including transcatheter aortic valve replacement eligibility in low-risk patients across 37 advanced economies. Methods and Results—: Four systematic searches were conducted across MEDLINE, EMBASE, and the Cochrane database for studies evaluating disease prevalence, severity, decision making, and survival in patients with aortic stenosis. Estimates of disease prevalence and treatment eligibility were calculated using stochastic simulation and population data for the 37 countries comprising the International Monetary Fund's advanced economies index. Fifty-six studies comprising 42 965 patients were included across 5 domains: prevalence, severity, symptom status, treatment modality, and outcome. The pooled prevalence in the general population aged 60 to 74 years and >75 years was 2.8% (95% confidence interval [CI], 1.4%–4.1%) and 13.1% (95% CI, 8.2%–17.9%), respectively—corresponding to an estimated 16.1 million (95% CI, 12.2–20.3) people in 37 advanced economies. Of these, an estimated 3.2 million (95% CI, 2.2–4.4) patients have severe aortic stenosis with 1.9 million (95% CI, 1.3–2.6) eligible for surgical aortic valve replacement. There are ≈485 230 (95% CI, 284 550–66 7350) high-risk/inoperable patients, 152 690 (95% CI, 73 410–263 000) intermediate-risk patients, and 378 890 (95% CI, 205 130–610 210) low-risk patients eligible for transcatheter aortic valve replacement. Conclusions—: With a prevalence of 4.5%, an estimated 16.1 million people aged ≥60 years across 37 advanced economies have aortic stenosis. Of these, there are ≈1.9 million patients eligible for surgical aortic valve replacement and 1.0 million patients eligible for transcatheter aortic valve replacement. Abstract : Supplemental Digital Content is available in the text.